Atomistic-Benchmarking towards a protocol development for rapid quantitative metrology of piezoelectric biomolecular materials. (December 2020) - O'Donnell, Joseph; Guerin, Sarah; Makam, Pandeeswar; Cazade, Pierre-Andre; Haq, Ehtsham Ul; Tao, Kai; Gazit, Ehud; Silien, Christophe; Soulimane, Tewfik; Thompson, Damien; Tofail, Syed A.M.
Highlights: Biomolecular crystals have enormous potential as low-cost, biocompatible piezoelectric materials. PFM coupled with DFT enables high-throughput, quantitative characterisation of biomolecular piezoelectrics. A statistical approach and best practice techniques allows unambiguous interpretation of PFM data. Abstract: Biomolecular crystals are an emerging class of piezoelectric materials that are both biocompatible and biodegradable, which enables their use in biomedical applications and smart devices while ensuring eco-friendly production and disposal. However, accurate quantification of the piezoelectric response of soft sub-micron crystals remains a significant challenge, as conventional piezoelectric measurement techniques are suited to ceramics, thin films, and polymers. Here, we demonstrate the use of a novel piezoresponse force microscopy (PFM) methodology for robust, reliable quantification of the electromechanical response of biomolecular crystals. As a strong test of high accuracy and precision, we show that PFM, integrated with quantum mechanical (QM) density functional theory (DFT) calculations, can distinguish the piezoelectric responses of near-isopiezoelectric amino acid crystals. We show that a statistical approach, combined with experimental best practices, provides effective piezoelectric coefficients of biomolecular single crystals accurately and unambiguously. This work opens the door to high-throughput screening and characterisation of natural and engineered soft piezoelectric crystals for eco-friendly energy harvesters and biodegradable medical implants, reducing dependence on lead-based and rare-earth-containing piezoelectric materials. Graphical abstract: Image, graphical abstract